Peran Orang Tua Sebagai Hubungan Yang Mendukung Dalam Keluarga di Stasiun Luwuk Bunter Paroki Joan Don Bosco Sampit - Vania Ulani; Abigail Jennifer Zoe Zevannya (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to determine the extent of the role of parents as liaison in the Luwuk Stasi family, Bunter Stasi Parish. Joan Don Bosco Sampit. In this research, parents become the main teachers in the family to strengthen the relationship between children and parents through good and smooth communication. The method used in this research is qualitative descriptive research with data collection techniques using observation, interviews and documents. The data analysis technique for this research uses the Miles and Huberman analysis technique which is divided into three stages, namely data reduction, data visualization (data research), and drawing conclusions/verification (drawing conclusions). The informants used in this research were 5 parents and 4 children. The results obtained from the research conducted by the author show that the role of parents in supporting family relationships at Luwuk Bunter Station is carried out well. A parent's role as a school principal is often to provide feedback and guidance to their children, such as encouraging them to pursue their dreams.